Problematika Kurikulum Merdeka di Sekolah Menengah Kejuruan - Kamila, Ana Tasya; Adawiyah, Siti; Leobety, Taroci Anna Erlis; Julianto, Indra Rasyid (Cahaya Smart Nusantara, 2025)
This research aims to discuss the problems and challenges faced by educators in implementing the independent curriculum in SMK. This research method uses descriptive qualitative with a literature study approach, and sorts out various relevant sources of information including conducting observations and interviews. The results of this study show that there are several problems faced in implementing the Merdeka Curriculum in every Vocational High School (SMK). Such as, lack of understanding and education about the independent curriculum, difficulty in implementing differentiated learning, and lack of facilities or facilities that support learning. To overcome the various problems that exist, steps are needed such as providing training on the implementation of the independent curriculum for teachers, encouraging teachers to use more varied and interactive learning methods, and the need for schools to improve facilities and infrastructure that support the learning process so that it can take place optimally.